Socioemotional wealth, family commitment and firm performance in private family owned businesses in Bangladesh / Mohammad Rezaur Razzak - Mohammad Rezaur, Razzak (2019)
Family business literature acknowledges that firms controlled by families are primarily driven by a set of goals that arise from social and emotional needs of the firm-owners that are non-economic in nature. However, the extant literature is yet to reach a nuanced understanding of how different dimensions of such family-centric goals, represented by the phenomenon; scoioemotional wealth (SEW), drive collective behavior of the owners such as family commitment to the firm and outcomes such as firm performance. This research builds on the premise that family firms vary in their goals and argues that the intensity of collective willingness of family firm owners to commit resource, time and effort towards the firm’s business goals depend on which of the dimensions of SEW (i.e., family control and influence, family identification with firm, binding social ties of the family, emotional attachment and renewal of family bonds through dynastic succession) are emphasized by the owners. The theoretical lens used to propose a conceptual link between dimensions of SEW as antecedents of family commitment and firm performance as its’ outcome, lies at the confluence of the socioemotional wealth theory and the stakeholder theory. The study examines how the antecedents and outcome of family commitment interact with each other, where family commitment is posited to be a mediator between SEW and firm performance. The research also considers the moderating effect of generational-incharge and professionalization in the above relationships. Leveraging arguments from past empirical works, seventeen (17) hypotheses are posited. The research being a quantitative study relied on self-administered survey method to obtain primary data from 357 medium-to-large privately held family firms involved in manufacturing of ready-made garments in Bangladesh. To conduct multivariate analysis and to test the hypotheses structural equation modeling (SEM) was deployed using SmartPLS (v.3.2) to examine the structural model and path model. The results indicate that 5 hypotheses out of 17 are not supported by the data. The findings also indicated that among the five dimensions of SEW, only the relationship ‘binding social ties of the family’ and family commitment was not significant. The other four dimensions of SEW all had significant association with family commitment. The mediation analysis indicated that all paths were significant except for the path with binding social ties. The moderating effect of generation in control was determined using multi-group analysis that showed that impact of family identification and binding social ties on family commitment was higher in the subsequent-generation compared to the founder-generation. The moderation analysis for professionalization on the relationship between family commitment and firm performance was strong and significant. From the theoretical perspective determining a consistent and predictable link between family-centric goals and firm-centric outcomes is currently a major goal of family business scholars seeking to develop a theory of family business. The role of behavior such as family commitment in the aforesaid link shows that the construct may have a vital role in the theoretical discourse. For industry practitioners a finer-grained understanding of how each dimension of SEW interacts with behavior and outcome, presents important clues for owners, investors and policy makers.